Pengaruh Pendidikan Teman Sebaya (Peer Group Education ) Terhadap Kualitas Hidup Lansia Dengan Hipertensi di Posyandu Lansia Wilayah Kerja Puskesmas Teluk Rendah Kabupaten Tebo - Nurhayati (Universitas Adiwangsa Jambi, 2023)
Background : Hypertension has an impact on the dimensions of quality of life, namely the physical, psychological and social dimensions. One form of management/activity to improve the quality of life of the elderly is peer group education. Peer group education is an educational method consisting of individuals or groups who present information to peers. Methods: The design of this research is a quasi-experimental research (quasi-experimental) with a Pre Test-Post Test with Control Group Design. The sample in this study were all elderly people who actively visited the posyandu for the elderly in the working area of ​​the Teluk Low Health Center, Tebo Regency in 2022. Data collection was carried out twice, namely before education (pretest) and after education (posttest). Univariate analysis using the frequency distribution and bivariate analysis using the Wilxocon signed test. Results: The results showed the value of sig. (2-tailed) 0.000<0.05, it means that there is a difference between the quality of life of the elderly with hypertension for the pretest and posttest peer group education. sig value. (2-tailed) 0.000<0.05, it means that there is a difference between the quality of life of elderly patients with hypertension for pretest and posttest giving leaflets. Conclusion: It is hoped that it can provide clear and complete information to elderly hypertensive patients and their families about hypertension treatment and how to treat hypertension, in addition to being a source of information in providing nursing care.